MiR-103 regulates the angiogenesis of ischemic stroke rats by targeting vascular endothelial growth factor (VEGF) - Fu-Ping Shi; Xue-Hong Wang; Hong-Xin Zhang; Meng-Meng Shang; Xiao-Xi Liu; Hai-Min Sun; Yue-Ping Song (Iranian Journal of Basic Medical Sciences, 2018)
Objective(s): To investigate the effect of miR-103 on the angiogenesis of ischemic stroke rats via targeting vascular endothelial growth factor (VEGF) at the molecular level. Materials and Methods: Rat models had received the middle cerebral artery occlusion (MCAO) or sham operation before grouping, and cell models of oxygen-glucose deprivation (OGD) were performed. FITC-dextran, matrigel, and Trans-well assays were used to evaluate the vascular density, tube formation, and cell migration respectively. The expression levels of miR-103 and VEGF were detected by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting. Dual-luciferase assay was used for analyzing the targeting relationship between miR-103 and VEGF. Results: We found the reduced miR-103 in rats after MCAO. Down-regulating miR-103 with the miR-103 inhibitor enhanced VEGF, ameliorated the neurological scores, decreased infarct volume, and increased vascular density in rats after MCAO. Besides, in OGD human umbilical vein endothelial cells (HUVECs), inhibition of miR-103 could promote the increase of tube length and the migration of cells. Additionally, we found that miR-103 could directly target VEGF and thereby lead to the down-expression of VEGF. Meanwhile, si-VEGF could reverse the effect of miR-103 inhibitor on angiogenesis in rats subjected to MCAO. Conclusion: Inhibition of miR-103 could promote ischemic stroke angiogenesis and reduce infarction volume via enhancing VEGF, which provides a new target for the clinical treatment of ischemic stroke.